Pengembangan Modul Praktikum Smart Relay Berbasis Problem Based Learning untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Instalasi Motor Listrik - Indri Setianingrum; Subuh Isnur Haryudo (International Forum of Researchers and Lecturers, 2026)
This study aims to evaluate the validity, effectiveness, and practicality of developing problem-based teaching materials for improving student learning outcomes. The research focuses on a practical module for the subject of electric motor installation at SMKN 1 Driyorejo, where interviews and needs assessment revealed issues such as teacher-centered learning and limited student resources, primarily relying on notebooks. These factors have hindered optimal learning outcomes. The development of problem-based learning modules was intended to address these issues and improve cognitive, affective, and psychomotor learning outcomes. The research follows a Research & Development (R&D) approach with four steps: 1) Define, 2) Design, 3) Develop, and 4) Disseminate, using a one-shot case study trial design. The study involved 30 students of grade XI TITL 1 at SMKN 1 Driyorejo. Results showed the module’s validity at 3.66, practicality based on student responses at 89.25, and effectiveness with cognitive, psychomotor, and affective outcomes of 84.93, 89.40, and 94.00, respectively. These findings suggest that the problem-based practical module is valid, practical, and effective for improving student learning outcomes across various domains.